Overall safety of relamorelin in adults with diabetic gastroparesis: Analysis of phase 2a and 2b trial data. Issue 11 (17th April 2020) - Camilleri, Michael; Lembo, Anthony; McCallum, Richard; Tourkodimitris, Stavros; Kemps, Lara; Miller, Matthew B.; Bertelsen, Kirk; Iacob, Alexandru
Summary: Background: Relamorelin, a pentapeptide ghrelin receptor agonist, accelerated gastric emptying significantly and improved symptoms in adults with diabetic gastroparesis in phase 2 trials. Aim: To assess the safety and tolerability of relamorelin across phase 2 trials. Methods: Safety assessments in patients aged 18‐75 years (weight, adverse events [AEs] and laboratory tests) from two randomised, double‐blind phase 2 trials (NCT01571297, NCT02357420; results published previously) were reviewed descriptively. Analysis of covariance assessed treatment effect on glycated haemoglobin (HbA1c) and blood glucose post hoc . Phase 2a and 2b trial durations were, respectively, 4 weeks (relamorelin 10 µg once or twice daily [b.d.] or placebo b.d.) and 12 weeks (relamorelin 10, 30 or 100 µg or placebo b.d.) with 1‐ and 2‐week, single‐blind placebo run‐ins. Results: Among 204 phase 2a and 393 phase 2b patients, respectively, 67% and 62% were female, and 88% and 89% had type 2 diabetes. Proportions of patients reporting serious AEs were similar across treatment groups, as were those with ≥1 treatment‐emergent AE (TEAE). TEAE‐related discontinuations were proportionally higher in relamorelin groups than placebo. Of 12 serious TEAEs in phase 2a, none occurred in >1 patient. In phase 2b, five serious TEAEs were reported in >1 patient, and one (100 µg) died (urosepsis), all unrelated to relamorelin. In phase 2b, increased HbA1c and fasting blood glucose levels were dose‐related ( P  < 0.0001 and P  = 0.0043, respectively). Conclusions: Relamorelin showed acceptable safety and tolerability in phase 2 trials. Relamorelin may elevate blood glucose: this should be managed proactively in relamorelin‐treated patients.